Development of on-farm structures and water delivery management model for improved rice irrigation practices, Tanjung Karang, Malaysia - Abdullah, Mohd Yazid (2016)
This pilot project study was conducted in Tanjung Karang Rice Irrigation Scheme,Selangor. The problems of the tertiary canal and on-farm water management in the scheme are related to the design of the tertiary canal; structures employed and water delivery management system for different modes of irrigation requirement. Other problems were related to the design and distribution of the existing structures along the tertiary canal and length of concrete canal measured up to seven kilometer serving up to 230 paddy lots caused the difficulties in delivering water timely, equitably and adequately to the whole canal length for different water delivery modes. As to overcome these problems, this study proposed development of three new on-farm structures and water delivery management models. Three structures in the tertiary irrigation canal and on-farm levels which were developed and evaluated in this study are: (1) flexible field offtake and automated float type flow control valve structure; (2) tertiary canal water level regulator or check structure and (3) field drainage outlet control structure. This water delivery management model was developed for four modes of irrigation supply for rice irrigation requirements, namely presaturation, second flooding, supplementary and termination of irrigation supply. The developed structures were tested in the laboratory and at the pilot project site for performance in terms of suitability and functionality in water delivery to obtain their accuracy, sensitivity and flexibility in different water delivery modes. The on-site evaluation were conducted to evaluate their performance in water delivery for different delivery modes, effectiveness in improving farm related activities in rice production and overall crop planting duration. The tests of these structures showed encouraging results for their respective functions in improving water delivery management in tertiary canal and on farm rice irrigation system. The most outstanding result of the laboratory tests was the stable and close to linear nature of flow through the flexible field offtake, for flow rate up to 10 liter/sec and maximum delivering capacity of up to 22 liter/sec. The results indicated its suitability to function as a flow measurement and flow control structures to provide a stable and accurate water delivery for supplementary irrigation and meet the flexibility of faster delivery for presaturation and second flooding other irrigation practices for rice cultivation.Sensitivity analysis of the offtake indicated that there was about 175 mm allowable water level fluctuation that provide flexibility and advantage to deal with the possible different in gate submergence in the canal operation or other reasons. Improved presaturation water delivery with the utilization of the newly developed flexible field offtake was based on the fact that faster water delivery in a shorter duration has reduced the amount of water required for presaturation. Through the utilization of the developed delivery management model for supplementary irrigation, the advantages of minimizing perturbation in tertiary canal flow, reducing farmers’ task in managing on farm irrigation practice, harvesting and capturing rainfall in paddy fields as well as controlling the run off flow from irrigation and rainfall to the drainage system could all be realized. It was successfully proven that the developed model with the support of efficient farm machinery service provider and responsive farmers result in shorter presaturation duration, saving a significant amount of water, and also shortened the overall duration of seasonal rice production significantly.